Stressors experienced by injured athletes (Journal of Sports Sciences, 2012)
The purpose of this study was twofold: (a) to examine the stressors experienced by injured athletes during three phases of their recovery from sport injury, and (b) to explore the differences in the stressors experienced by team as compared to individual-sport athletes. Participants comprised previously injured high-level rugby union players (n = 5) and golfers (n = 5). Semi-structured interviews were used to explore the stressors participants experienced during three phases of injury (onset, rehabilitation and return to competitive sport). Within- and cross-case analyses showed that athletes experienced sport, medical/physical, social and financial stressors. There were a number of differences in the stressors experienced across the three phases and between team and individual-sport athletes. Findings have important implications for the design and implementation of interventions aimed at managing the potentially stressful sport injury experience and facilitating injured athletes' return to competitive sport.